Considerations on the way towards professional-scientific education - Wildt, Johannes [Verfasser]; Rein, Volker [Verfasser] (My University, 2022)
The closing contribution draws some conclusions of the previous 18 contributions of the anthology. To promote further discussion on the topic of professional-scientific education ten theses with the following headings are presented: 1. The relationship between academic education, occupation and societey; 2. Specialised or generalised academic education?; 3. On the polyvalence of scientific education in the medium of science and profession; 4. The relationship between academic education and competence; 5. Research-based and project-oriented learning - teaching concepts for combining scientific and professional education; 6. Dealing with the structural difference of types of knowledge in the context of professional-scientific activity: a professionalisation dilemma; 7. Education in context: on the correlation of theory and practice; 8. Participatory curriculum development in the scientific study programmes; 9. Interdisciplinary and transdisciplinarity and the design of education in the medium of science; 10. Professional-scientific learning for socially responsible action. (BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 1.4 Hochschulbildung; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; 370; Berufsbildung; Hochschulbildung; Verzahnung beruflicher und hochschulischer Bildung; Anrechnung von Bildungsleistungen; Lernergebnisorientierung; Kompetenzorientierung; Professionalisierung; Theorie-Praxis